De la nécessité d’une approche linguistique et historique dans les débats sur l’immigration - Jean-Louis Chiss (Recherches en didactique des langues et des cultures)
This paper is written in reaction to Soriano’s paper that deals, as a sociologist, with the subject of migrant children in their family and at school. My project is to tackle head-on the relationships that migrant children have with languages beyond the binary system of family language and schooling language. To achieve it, we need to look at terminological problems, the context and the history.